1996
DOI: 10.1046/j.1526-4610.1996.3605307.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide, Endothelin‐1, and Transcranial Doppler in Migraine. Findings in Interictal Conditions and During Migraine Attac

Abstract: The role of vascular phenomena taking place during an attack of migraine are poorly understood. The aim of this study was to measure systemic levels of nitric oxide and endothelin-1, two of the most potent vasoactive mediators known, and to assess vasomotor responses through transcranial Doppler ultrasound monitoring in patients suffering from migraine without aura, both during the headache event and in headache-free periods as well as after pharmacologically induced pain relief. Seven patients (mean age 31.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
22
2
Order By: Relevance
“…20 Nattero et al demonstrated higher serum NO levels during the migraine attack, but their patient group was very small (n = 7). 21 Similar to the findings of our study, several other studies reported insignificant NO À 2 and NO À 3 changes in plasma, 22 leukocytes and platelets 23 during the interictal period in patients with migraines as compared to the control group. However, none of these studies evaluated plasma ADMA levels in addition to NO metabolites.…”
Section: Discussionsupporting
confidence: 92%
“…20 Nattero et al demonstrated higher serum NO levels during the migraine attack, but their patient group was very small (n = 7). 21 Similar to the findings of our study, several other studies reported insignificant NO À 2 and NO À 3 changes in plasma, 22 leukocytes and platelets 23 during the interictal period in patients with migraines as compared to the control group. However, none of these studies evaluated plasma ADMA levels in addition to NO metabolites.…”
Section: Discussionsupporting
confidence: 92%
“…The earliest findings of a slight increase in the peripheral levels of nitrites, consistent with a parallel increase in ET-1 levels, came from a study by Nattero et al [48] on migraine patients examined in interictical periods and during attacks. There is also evidence of an increase in nitrite levels in peripheral blood of migraine patients examined interictally [49].…”
Section: No and Cerebral Spreading Depressionmentioning
confidence: 84%
“…They suggest that their results motivate studies of endothelin as a potential novel therapy for neuropathic pain. Nattero et al 1996 [23] showed that plasma endothelin-1 concentrations decreased during migraine attacks. Endothelin was found to be associated with pain in the present study, as there were lower endothelin levels in the ''pain'' group as compared to ''no pain''.…”
Section: Immune Markers and Neuropeptidesmentioning
confidence: 99%